Genomic analysis of pancreatic juice DNA assesses malignant risk of intraductal papillary mucinous neoplasm of pancreas. (21st June 2019) - Mateos, Raúl N.; Nakagawa, Hidewaki; Hirono, Seiko; Takano, Shinichi; Fukasawa, Mitsuharu; Yanagisawa, Akio; Yasukawa, Satoru; Maejima, Kazuhiro; Oku‐Sasaki, Aya; Nakano, Kaoru; Dutta, Munmee; Tanaka, Hiroko; et al.
Abstract: Intraductal papillary mucinous neoplasm (IPMN) of pancreas has a high risk to develop into invasive cancer or co‐occur with malignant lesion. Therefore, it is important to assess its malignant risk by less‐invasive approach. Pancreatic juice cell‐free DNA (PJD) would be an ideal material in this purpose, but genetic biomarkers for predicting malignant risk from PJD are not yet established. We here performed deep exome sequencing analysis of PJD from 39 IPMN patients with or without malignant lesion. Somatic alterations and copy number alterations (CNAs) detected in PJD were compared with the histologic grade of IPMN to evaluate their potential as a malignancy marker. Somatic mutations of KRAS, GNAS, TP53, and RNF43 were commonly detected in PJD of IPMNs, but no association with the histologic grades of IPMN was found. Instead, mutation burden was positively correlated with the histologic grade ( r  = 0.427, P  = 0.015). We also observed frequent copy number deletions in 17p13 ( TP53 ) and amplifications in 7q21 and 8q24 ( MYC ) in PJDs. The amplifications in 7q21 and 8q24 were positively correlated with the histologic grade and most prevalent in the cases of invasive carcinoma ( P  = 0.002 and 7/11; P  = 0.011 and 6/11, respectively). We concluded that mutation burden and CNAs detected in PJD may have potential to assess the malignant progression risk of IPMNs. Abstract : Significantly amplified regions (red) and significantly deleted regions (green) by patient and by the histologic grade of IPMNs are shown. The 7q21 amplification and 8q24 amplification (MYC) showed significant association with invasive carcinoma of IPMN.